2014
DOI: 10.1007/s12687-014-0205-1
|View full text |Cite
|
Sign up to set email alerts
|

How people in Benin assess a couple’s risk of having a baby with sickle cell disease

Abstract: Sickle cell disease (SCD) is a genetic disease resulting from the inheritance from both parents of a mutant hemoglobin gene. Its occurrence can, at best, be prevented, and its daily life consequences can, at least, be limited. As the mutant gene is recessive, it should be useful for people living in countries where SCD is endemic to know their own genetic status and that of their actual or potential partner in order to assess the risk of having a baby with SCD. The present study aimed at examining how a conven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…Nevertheless, the individual difference groupings identified by cluster analysis are not automatically real, but must, in the end prove their lasting value in validation studies linking the clusters to variables outside the classification data. Throughout this chapter we emphasized that the clusters were internally coherent, with clear process interpretations and developmental trends as also found in other domains (Gamelin et al, 2006, Zounon et al, 2015Muñoz Sastre et al, 1998). Studies in other domains found meaningful learning effects, such that participants moved from less to more advanced clusters after feedback (Liegeois et al, 2003).…”
Section: Discussionsupporting
confidence: 57%
“…Nevertheless, the individual difference groupings identified by cluster analysis are not automatically real, but must, in the end prove their lasting value in validation studies linking the clusters to variables outside the classification data. Throughout this chapter we emphasized that the clusters were internally coherent, with clear process interpretations and developmental trends as also found in other domains (Gamelin et al, 2006, Zounon et al, 2015Muñoz Sastre et al, 1998). Studies in other domains found meaningful learning effects, such that participants moved from less to more advanced clusters after feedback (Liegeois et al, 2003).…”
Section: Discussionsupporting
confidence: 57%
“…In Benin, as in most sub-Saharan African countries, systematic screening for SCD is not a common practice as most sickle cell-trait carriers often are asymptomatic. This lack of systematic screening increases the rate of high-risk marriages and thus maintains the prevalence of the disease in the population (Alhamdan et al, 2007;Zounon et al, 2015). Therefore, the first challenge in the fight against SCD remains primary prevention through strategies that use systematic screening for SCD in the population and doing this in strict compliance with ethical rules.…”
Section: Potential Solutionsmentioning
confidence: 99%
“…Second, there is a need to improve health education programs for the population, more efforts are needed for the counseling of couples, and good management in timing screening could decrease high-risk marriages and ultimately reduce the prevalence of the disease. In this perspective, public authorities, as well as religious and traditional authorities, can play important roles (Alhamdan et al, 2007;Rahimy et al, 2009;Zounon et al, 2015;Ezugwu et al, 2019).…”
Section: Potential Solutionsmentioning
confidence: 99%
“…Sickle cell anemia (SCA) is an autosomal recessive blood disorder [1]. Carriers who have one copy of the mutant hemoglobin S gene typically have no symptoms.…”
Section: Introductionmentioning
confidence: 99%